Effects of Energiewende - Štibraný, Bernard (2023)
The bachelor´s thesis concerns itself with the topic of the extensive renewable energy transition that is currently taking place in the Federal Republic of Germany. It aims to evaluate how well the individual targets for the year 2020 have been met and what issues arose during the first decade of Energiewende´s existence. Furthermore, it concentrates in greater detail on the issue of intermittency of variable renewable sources of energy. It does this by evaluating what impacts did the increase in the share of renewable energy sources in the electricity generation mix have on wholesale electricity prices and their volatility on the German electricity market. Additionally, the thesis examines the changes in electricity imports and exports between the Federal Republic of Germany and its neighbours.